THE IMPLEMENTATION OF THEME-BASED TEACHING TO IMPROVE YOUNG LEARNERS' ENGLISH VOCABULARY - Fathimah, Nida Mujahidah (2013)
This research paper entitled "The Implementation of Theme-Based Teaching to Improve Young Learners' English Vocabulary" was conducted to find out how the implementation of theme-based teaching could improve young learners' English vocabulary and the students' responses towards its implementation. This research was carried out in one primary school in Bandung involving 32 fifth grade students. This study employed classroom action research by conducting vocabulary assessment, observation and questionnaire to collect the data. Based on the research findings, the theme-based teaching improved students' vocabulary in terms of word identification, word meaning, and word use. It was also found that the students' responses were highly positive towards the implementation of theme-based teaching. For further research, it is suggested for teachers who want to apply this approach to provide themes that are familiar with the students and have been discussed together in the classroom to increase students' level of interest. Moreover, it is also suggested to conduct research in a longer period to give better result and better picture of the implementation of theme-based teaching to improve young learners' English vocabulary.